Neuromodulation of Executive Circuits - Evelyn K. Lambe (Frontiers Research Topics, 2016)
High-order executive tasks involve the interplay between frontal cortex and other cortical and subcortical brain regions. In particular, the frontal cortex, striatum and thalamus interact via parallel fronto-striatal "loops" that are crucial for the executive control of behavior. In all of these brain regions, neuromodulatory inputs (e.g. serotonergic, dopaminergic, cholinergic, adrenergic, and peptidergic afferents) regulate neuronal activity and synaptic transmission to optimize circuit performance for specific cognitive demands. Indeed, dysregulation of neuromodulatory input to fronto-striatal circuits is implicated in a number of neuropsychiatric disorders, such as schizophrenia, depression, and Parkinson's disease. However, despite decades of intense investigation, how neuromodulators influence the activity of fronto-striatal circuits to generate the precise activity patterns required for sophisticated cognitive tasks remains unknown. In part, this reflects the complexity of the cellular microcircuits in these brain regions (i.e. heterogeneity of neuron subtypes and connectivity), cell-type specific expression patterns for the numerous receptor subtypes mediating neuromodulatory signals, and the potential interaction of multiple signaling cascades in individual neurons. This Research Topic includes 10 original research articles and seven review articles addressing the role of neuromodulation in executive function at multiple levels of analysis, ranging from the activity of single voltage-dependent ion channels to computational models of network interactions in cortex-striatum-thalamus systems.